KONSEP PARENTING DALAM KELUARGA MUSLIM - Abdul Goffar; Saeful Kurniawan (Fakultas Tarbiyah, Universitas Ibrahimy, 2018)
Parents who have children will crave their child to be successful. Success in any case, in morals, education, career, and so forth.Because a child is predicted to be their successor and successor (parent) in this life. Naturally there is no parent in the world who wants them to suffer, deprived, and unhappy. So many parents with their strengths to make the future of their children. In development and development to adulthood, children have basic needs that must be met, that is spiritual and physical needs. To meet these two needs required coaching, guidance, and attention that is needed. Although every newborn child has brought capacity and development potential, this development will not work on its own without the help of an adult, a family (a parent). For more details in this paper, we will discuss parenting concepts (parenting, parenting mode, parenting methods) and also talk about children’s education in the family, children’s education stage, children’s education materials, family roles in education.